Uso de tablets y resolución de problemas en estudiantes del sexto ciclo de secundaria del área de matemática en la Institución Educativa C.R.F.A Santa Teresa primera zona Yavarí Ramón Castilla 2021 - Panaifo Panaifo, Marilissa (2023)
This section briefly presents the most important aspects of this research whose general objective was to relate the use of tablets to problem solving in students of the sixth cycle of secondary school in the area of mathematics at the C.R.F.A Educational Institution in Santa Teresa in Yavarí, Province of Ramón Castilla during 2021. For this purpose, the type of relational research was applied, and its design was: Bivariate, field and transectional. The research subjects were 31 students who constituted the population and sample, they were given a questionnaire using the survey technique, in addition there was an observation guide for data collection, the instruments were validated in their expert opportunity. The findings found show that according to Spearman's rho correlation coefficient = 0.410*, p = 0.022, there is a low significant direct relationship between the use of tablets and problem solving in students of the sixth cycle of secondary school in mathematics at the Educational Institution. C.R.F.A of the town of Santa Teresa, Yavarí, Ramón Castilla.